Identification and management of inverted or everted edges of traumatic tympanic membrane perforations - Lou,Zhengcai (2019)
Abstract Introduction: Most of traumatic tympanic membrane perforations have inverted or everted edges, however, the effects of inverted and everted edges on the spontaneous healing of the eardrum remain controversial. Objective: We investigated the influence of inverted or everted edges on the spontaneous healing of traumatic tympanic membrane perforations. Methods: The clinical records of patients with a traumatic tympanic membrane perforations who met the study criteria were retrieved and categorized into two groups, based on whether the eardrum was inverted or everted. The features along the edge of each inverted or everted eardrum were described using 30º and 70º endoscopes. Results: In total, 196 patients (196 ears) met the inclusion criteria; of these, 148 had inverted or everted eardrums while 48 did not. Of the 148 patients with inverted or everted eardrums, the perforation edges were everted in 77 patients, inverted in 44 patients, drooping in 17 patients, and both inverted and everted in 10 patients. The perforation shape was triangular in 18.9% of patients, sector-shaped in 11.5%, kidney-shaped in 14.2%, ovoid in 20.3%, and irregularly shaped in 35.1% of patients. The difference was not significant between the with and without inverted/everted eardrum edges groups in terms of the closure rate or closure time. Similarly, the difference was not significant between the with and without edge approximation groups in terms of the closure rate or closure time at the end of the 12-month follow-up period. Conclusion: This study suggests that endoscopic inspection can clearly identify inverted/everted eardrum edges using 30º and 70º endoscopes. The edge is glossy in inverted/everted eardrums, whereas the edge is rough and irregular in non-inverted/everted cases. The inverted/everted eardrums gradually became necrotic, but this did not affect the healing process. Additionally, edge approximation did not improve the healing outcome of traumatic tympanic membrane perforations.